Larangan Sholat bagi Orang Mabuk : Studi Penafsiran Ahkam pada Q.S An-Nisa (4) : 43 - Andy, Safria; Sembiring, Ghita Kinanti Pratiwi; Nasution, Wildan Hamdani (ANWARUL, 2022)
A person who has been burdened by the law is called a Mukallaf who is obliged to carry out the prayer orders and not neglect Allah's commands. Prayer in Islam is a natural activity of worship that has the highest degree compared to other worship activities. Prayer has a very large measure for the religion of Islam, and is the most important worship as long as mankind lives on earth. However, there is a prohibition on praying for people who are drunk as explained in the study of the interpretation of ahkam in Q.S An-Nisa (4): 43. The research was conducted using a type of library research, where the data collection method was in the form of scientific literature books relating to the matter to be discussed. in research. The source of the data in this study is the Tafsir of Ahkam verses. From the results of research showing that all disasters begin with drunkenness, it has been proven throughout the course of human history that drunkenness from drinking khamr can cause havoc. Intoxicated drinkers may act in ways that are contrary to social, legal, and religious norms. So according to Allah, when drunk is not allowed to pray. This restriction not only prohibits prayer, but also states that prayer said while drunk is invalid.